Sistem Pendukung Keputusan Proses Kenaikan Jabatan dan Perencanaan Karir Pada PT. ABC Dengan Metode Profile Matching - Supiyandi Supiyandi; Muhammad Zen (UIN Sumatera Utara, 2019)
In accordance with the regulations set out in a company in carrying out the promotion process, criteria are needed to determine who will be selected to fulfill the position especially in the sales manager division. In the process of determining this position a decision support system is needed. One method that can be used for Decision Support Systems is to use the Profile Matching method. In this study, a case will be raised, namely finding the best solution based on employee competencies in a company using the Profile matching method. This method was chosen because it is able to select the best candidates from a number of existing employees, in this case the intended candidates are employees who are entitled to occupy positions available based on the specified criteria. The research was conducted by looking for weight values for each attribute, such as examples of aspects of intellectual capacity, aspects of work attitudes, and behavioral aspects, then a ranking process was conducted that would determine the optimal alternative, namely the best employees.Keywords: Profile Matching, Competence, Promotion, Decision Support Sytem